Degree Square Subtraction Spectra and Energy - Jyoti Sachin Macha; Sumedha Narayan Shinde (IndoMS, 2022)
This paper defines and computes the degree square subtraction matrix, its characteristic polynomial and spectra in terms of the first Zagreb Index. We explore its bounds for spectral radius and energy.